Colorectal endoscopic submucosal dissection in the West: A systematic review and meta-analysis - Singh, Ritu Raj; Nanavati, Julie; Gopakumar, Harishankar; Kumta, Nikhil A (Endoscopy International Open, 2023)
Background and study aims The advantages of endoscopic submucosal dissection (ESD) over endoscopic mucosal resection for large colorectal neoplasms are well established; however, the technical challenges and lack of adequate training in ESD limit its widespread adoption in Western countries.Methods A literature search was performed in Medline, Embase, Web of Science, and the Cochrane Library for studies conducted in non-Asian countries evaluating the effectiveness of colorectal ESD. A random effects model was used to obtain pooled en bloc, R0 resection rates, and adverse events (AEs).Results Thirty-three studies comprising 3,958 ESD procedures met the inclusion criteria. Of the polyps, 96.7% (2,817 of 2913) were ≥ 2 cm. Pooled en bloc resection (31 studies), R0 resection (29 studies), and curative resection rates were 84.6% (95% confidence interval [CI] [83.3%–85.9%]), 75.6% (95% CI [74.1%–77.0%]), and 81.9% (95% CI [78.6%–84.9%]), respectively. Surgery for invasive cancer was performed in 4.8% (23 studies). ESD-related perforation (25 studies) was observed in 5.5% and bleeding in 4.1% (delayed bleeding 3.4%). 1.8% of patients underwent surgery for procedure-related complications. A high degree of heterogeneity was observed for en bloc resection, R0 resection, and curative resection. Heterogeneity for AEs (perforation [I2 13%], delayed bleeding [I2 30%], and overall bleeding [I2 49%]) was low to moderate.Conclusions The effectiveness of colorectal ESD for large colorectal polyps and early colorectal cancers is improving in Western countries, and recent resection rates are comparable to that seen in Asia. Colorectal perforation is still observed in about 5% of ESD; however, < 2% of patients need emergency surgery for AEs.
Keywords: Colorectal cancer; Endoscopy Lower GI Tract; Endoscopic resection (polypectomy, ESD, EMRc, ...)